Study guides

☆☆

Q: Simplify 3a plus 5 plus 2a plus 6?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

The idea here is to combine terms that have the same variable (or, in more complicated cases, the same combination of variables). For example, 3a + 2a is the same as 5a.

5 x 3a= 15a

-8a + 3a = (-8 + 3)a = (5)a = 5a

9a +8 -2a -3 -5a = 2a +5

It is: 7a+1 when simplified

Related questions

If 3a+5=5a+3, then: 3a+5 - 3a = 5a+3 - 3a 5=2a+3 5 - 3=2a+3 - 3 2=2a a=1

3a + 4b - 5 - 1a + 7b + 3 - 1b 2a + 10b - 5 + 3 2a + 10b - 2

(6a3 - 19a2 + 15a)/(2a - 3) = a(6a2 - 19a + 15)/(2a - 3) = a(2a - 3)(3a -5)/(2a -3) = a(3a - 5)

depends what 'a' =

2a-3+4b-2a-b-2a-b-3+5 Can be simplified to: 3b-1

3b -1

2a + 4b - 52a + 4b - 52a + 4b - 52a + 4b - 5

5a - 5 = 7 + 2a ( subtract 2a from both sides) 3a - 5 = 7 (add 5 to both sides) 3a = 12 ( divide both sides by 3) a = 4

2a+5

The problem 3a-1 and 2a-5 is greater by 7. This is a math problem.

= 3 X 2 = 6 = a X a = a2 (a square) = 6a2 + 5 Answer

2a-5=-3a5a-5=05a=5a=0